Development of a model to predict room temperature based on room geometry using computational fluid dynamics - Al-Gailani, Mohammed W. Muhieldeen (2017)
Over the years, the growth in economic activities and the population increase in Malaysia have led to an increase in energy consumption in the home. The Uniform Building By-Law Act (UBBL) 1984 only recommends a minimum ceiling height in buildings. Overheating exists in Malaysian homes and the use of air conditioners is a short term solution that implies a higher use of energy to the government. The green building concept relies on a passive solution to lower energy consumption whereby innovative initiatives can be integrated into green buildings at the design stage. One passive method is to consider room geometry to achieve thermal comfort in a naturally ventilated tropical building. This study is concerned with the development of a model to predict room temperature using geometry in a residential building and so achieve thermal comfort inside the house. Data on the air temperature, air velocity and Relative Humidity were measured in 40 rooms in the in Klang Valley area as input data for the simulation work. FLUENT (CFD) software was selected for the simulation study where 3D geometry was modeled to simulate the air flow under turbulent k-ε standard, by including all the boundary conditions for the walls, the roof, the ceiling and the glass. The selected meshes are the hexhydro/map and the hexwedge/cooper with a 0.2 mesh size; these were used to collect accurate results. The room model that was generated had dimensions of Length: 4 m, Width: 3 m and Height: 2.6 m, instead of 2.5 m as illustrated in the UBBL, and this was validated with actual test rooms in the Klang Valley. The result shows the existing construction materials (concrete) for houses in Malaysia is suitable material for thermal condition via heat transfer (q), (k) thermal conductivity, (ΔT) temperature difference between inside and outside temperature and (V) is volume, according to the developed equation where is applicable to Malaysia and other tropical countries. The finding show the suitable height for all environmental conditionsis 3 m.